Bioactive Constituents from South American Prosopis and their Use and Toxicity - Schmeda-Hirschmann, Guillermo; Theoduloz, Cristina; Jiménez-Aspee, Felipe; Echeverría, Javier (Current Pharmaceutical Design, 2020)
Background: The pods from several South American Prosopis species have been considered relevant food in arid and semi-arid South America since prehistoric times. Traditionally the meal from the pods was processed to prepare different foods and beverages. Objective: The objective was to discuss literature from the archaeological evidence of use to study the chemistry and (bio)activity of the extracts and secondary metabolites occurring in different Prosopis food products. Methods: The review was carried out by searching electronic databases, including ScienceDirect, SciFinder, Scopus, Scielo, Google Scholar, PubMed and hand-search on literature. The review mainly covers studies performed in the year 1995-2019 and the first-hand experience of the authors. References on the historical and prehistorical uses of the natural resource were also included. Results: In the last decades, most studies on the edible South American Prosopis focused on the constituents of pods meal, traditional preparations and by-products. Total 45 flavonoids, ellagic acid derivatives, catechin and simple phenolics were identified. Alkaloids occur mainly in the leaves, that are not used for human nutrition but as food for domestic animals. Piperidine alkaloids, tryptamine, tyramine and β-phenethylamine were isolated and identified from several species. The (bio)activity studies included mainly the antioxidant effect, antiinflammatory and enzyme inhibition associated with metabolic syndrome. The products showed no toxicity or mutagenic effect. Conclusion: While data on the chemistry, some (bio)activities and toxicity are available for the pods meal and byproducts, little is known about the composition of the fermented Algarrobo beverages. Further studies are needed on the digestion of Algarrobo products both in humans and cattle.
Keywords: South American foods